PERANAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PEMBENTUKAN PERATURAN DESA DI DESA KRANDON KECAMATAN GUNTUR KABUPATEN DEMAK - Siti Rodhiyah; Muhammad Harir (Jurnal Pembaharuan Hukum, 2016)
The Village Consultative Council is a form of Democracy at the village level. Village consultative Council function to establish village regulations with village leader, accommodate and channel the aspirations of village communities. In this case the role of the Village Deliberation Agency which created village regulations with the Village Head in establishing the social civilization, economic and cultural.The research method uses sociological juridical approach, with object of study especially role of Village Consultative Council as partner of Village Head in establishing Village Regulation.The result of the research shows that the role of the village consultative council in the formation of village regulations in Krandon Village, Guntur District, Demak Regency is not optimal enough to extend the hand of the village because the village regulations that have been established in the last two years do not reflect the needs of the community and the community And the constraints affecting the legislative function of the village consultative council, as well as the factors that become obstacles in the preparation and stipulation of the protest, among others, the poor quality performance of the village apparatus and village consultative bodies, the lack of village budgets in every legislative process, the internal quality of the Village consultative council.